Generation of monoclonal antibodies to the anti-trypanosomal drug Samorin - Peregrine, A.S.; Eisler, M.C.; Flynn, J.N.; Katende, J.; Gault, E.A.; Kinabo, L.D.B.; Homes, P.H. (OAU/STRC, 1995)
Isometamidium chloride (Samorin, Trypanidium is a phenanthridine-aromatic amidine that is commonly used in cattle as a prophylactic agent against trypanosomiasis. Although the compound has been used for over 30 years, very little is known about its mode of action. Various workers have demonstrated that the molecule interferes with DNA polymerases purine nucleotide synthesis polyamine metabolism and mitochondrial type II topoisomerase .However, the contribution of such activities to the compound's anti-trypanosomal activity in vivo is not known. In the work presented here we describe the production and characterisation of a set of monoclonal antibodies (MAbs) that were raised against isometamidium. Such reagents constitute a potential tool for determining the site of action of isometamidium within trypanosomes. Two drug conjugates were synthesised for this work; an isometamidium-human serum albumin (HSA) conjugate was prepared as described by Kinabo and Bogan (1988). An isometamidium-porcine thyroglobulin (PTG) conjugate was prepared as described by Whitelaw et al. (1991). Thereafter, anti-isometamidium monoclonal antibodies were produced using two methods.